2022
DOI: 10.3390/foods11172709
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Cellulase-Hydrolyzed Deoiled Coconut Cake Powder as Wheat Flour Substitute in Cookies

Abstract: Deoiled coconut cake powder (DCCP) was hydrolyzed to reduce the ratio of insoluble/soluble dietary fiber (RIS) by partially converting insoluble dietary fiber to soluble using Celluclast 1.5 L, a commercial cellulase preparation in citrate buffer medium. Firstly, the influence of citrate buffer amount, enzyme concentration, pH, and retention time on the enzymatic hydrolysis efficiency was investigated. Then, response surface methodology (RSM) was employed to optimize the process in which the insoluble and solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Compared to traditional methods, lignocellulolytic enzymes offer several advantages, such as higher yields and reduced thermal damage to the products, making them highly favored in multiple industries [258]. Moreover, these enzymes can enhance the stability and texture and reduce the viscosity of fruit nectars and purees and even assist in the process of extracting olive oil [259]. Within the bakery industry, xylanases are particularly valuable as they soften the dough, delay crumb formation, increase volume, and improve overall quality by subjecting the hemicellulose in wheat flour to hydrolysis [260].…”
Section: Main Bodymentioning
confidence: 99%
“…Compared to traditional methods, lignocellulolytic enzymes offer several advantages, such as higher yields and reduced thermal damage to the products, making them highly favored in multiple industries [258]. Moreover, these enzymes can enhance the stability and texture and reduce the viscosity of fruit nectars and purees and even assist in the process of extracting olive oil [259]. Within the bakery industry, xylanases are particularly valuable as they soften the dough, delay crumb formation, increase volume, and improve overall quality by subjecting the hemicellulose in wheat flour to hydrolysis [260].…”
Section: Main Bodymentioning
confidence: 99%
“…The amount of force needed to break down the cookies was significantly reduced as a result of the increase in YCM flour addition. Additionally, the presence of fiber reduced the hardness of cookies, as occurred in the cookies incorporated in coconut cake powder [29].…”
Section: Texture Of Cookiesmentioning
confidence: 99%
“…It has also been found that asparaginase improved the sensory properties of sea buckthorn pomace biscuits and reduced acrylamide production (Kukurová et al., 2023). In addition, it has also reported the use of cellulase‐hydrolyzed deviled coconut biscuit powder to partially replace WF in the production of biscuits (Vo et al., 2022). Water released from the hydrolysis of dietary fibers by cellulases and pectinases bound to the gluten–starch network in dough and altered the gluten structural conformation (Hu et al., 2022).…”
Section: Introductionmentioning
confidence: 99%